2011
DOI: 10.2174/138955711795305335
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Dietary Flavonoid Kaempferol

Abstract: Epidemiological studies have revealed that a diet rich in plant-derived foods has a protective effect on human health. Identifying bioactive dietary constituents is an active area of scientific investigation that may lead to new drug discovery. Kaempferol (3,5,7-trihydroxy-2-(4-hydroxyphenyl)-4H-1-benzopyran-4-one) is a flavonoid found in many edible plants (e.g. tea, broccoli, cabbage, kale, beans, endive, leek, tomato, strawberries and grapes) and in plants or botanical products commonly used in traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
717
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,053 publications
(781 citation statements)
references
References 680 publications
14
717
1
9
Order By: Relevance
“…Numerous pre-clinical studies have shown that kaempferol exerts a wide range of pharmacological properties, such as antioxidant, anti-inflammatory, anti-cancer, cardioprotective, neuroprotective, anti-diabetic, anti-osteoporotic and anti-allergic activities. 18 Flavonols of kaempferol and quercetin inhibit IgEmediated release of pro-inflammatory IL-6, IL-8 and TNF-a from mast cells possibly through inhibition of intracellular calcium influx and PKC theta signaling, being suitable for the treatment of allergic and inflammatory diseases. 28 Our recent studies have demonstrated that kaempferol suppresses eosionphil infiltration and airway inflammation in airway epithelial cells and in mice with allergic asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous pre-clinical studies have shown that kaempferol exerts a wide range of pharmacological properties, such as antioxidant, anti-inflammatory, anti-cancer, cardioprotective, neuroprotective, anti-diabetic, anti-osteoporotic and anti-allergic activities. 18 Flavonols of kaempferol and quercetin inhibit IgEmediated release of pro-inflammatory IL-6, IL-8 and TNF-a from mast cells possibly through inhibition of intracellular calcium influx and PKC theta signaling, being suitable for the treatment of allergic and inflammatory diseases. 28 Our recent studies have demonstrated that kaempferol suppresses eosionphil infiltration and airway inflammation in airway epithelial cells and in mice with allergic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol is a strong antioxidant preventing oxidative cell damage and inhibiting oxidation of LDL and induction of inflammatory mediators involved in the initial steps of atherosclerotic plaque formation. 18,19 In our previous studies, 20,21 kaempferol suppressed eosionphil infiltration and airway inflammation in airway epithelial cells and in mice with allergic asthma. There are numerous studies dealing with inhibitory effects of polyphenols on airway dysfunction and disorders.…”
mentioning
confidence: 85%
“…17 Thus, benecial roles of kaempferol have been reported in inammation, hyperglycemia and diabetes using different in vitro and in vivo models. 18 In addition, some investigations concluded that the anti-inammatory activity of Helichrysum italicum may be explained by enzyme inhibition, free-radical scavenging activity and corticoid-like effects. 19 In this sense, our group previously demonstrated that helichrysum and grapefruit extracts ameliorated hyperglycemia by inhibiting a-glucosidase (a similar mechanism to acarbose) and a-amylase enzyme activities and by decreasing the SGLT1-mediated glucose uptake in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…and other human pathogenic bacteria. [22,23] Alstonville (T. lepidota) is used mostly as an ornamental plant due to their dark purple flowers with no medicinal usage previously reported. However, other species within the genus have been reported to possess various biological activities such as wound healing and to treat cataract.…”
mentioning
confidence: 99%